HOTAIR lncRNA promotes epithelial–mesenchymal transition by redistributing LSD1 at regulatory chromatin regions. (6th May 2021) - Jarroux, Julien; Foretek, Dominika; Bertrand, Claire; Gabriel, Marc; Szachnowski, Ugo; Saci, Zohra; Guo, Shuling; Londoño‐Vallejo, Arturo; Pinskaya, Marina; Morillon, Antonin
Abstract: Epithelial‐to‐mesenchymal transition (EMT) describes the loss of epithelial traits and gain of mesenchymal traits by normal cells during development and by neoplastic cells during cancer metastasis. The long noncoding RNA HOTAIR triggers EMT, in part by serving as a scaffold for PRC2 and thus promoting repressive histone H3K27 methylation. In addition to PRC2, HOTAIR interacts with the LSD1 lysine demethylase, an epigenetic regulator of cell fate during development and differentiation, but little is known about the role of LSD1 in HOTAIR function during EMT. Here, we show that HOTAIR requires its LSD1‐interacting domain, but not its PRC2‐interacting domain, to promote the migration of epithelial cells. This activity is suppressed by LSD1 overexpression. LSD1‐HOTAIR interactions induce partial reprogramming of the epithelial transcriptome altering LSD1 distribution at promoter and enhancer regions. Thus, we uncover an unexpected role of HOTAIR in EMT as an LSD1 decommissioning factor, counteracting its activity in the control of epithelial identity. SYNOPSIS: This study shows that HOTAIR lncRNA independently of PRC2 redistributes LSD1 along chromatin genome‐wide and thus impairs Lsd1 function in maintaining epithelial identity. HOTAIR lncRNA promotes migration of immortalized epithelial cells. The Lsd1‐binding domain, but not the PRC2‐binding domain, is essential for the HOTAIR‐dependent migration phenotype. HOTAIR displaces Lsd1 from its target enhancers and promoters in epithelial cells. Lsd1 dislocation in the presence of HOTAIR switches gene expression patterns to favor mesenchymal identity. Abstract : This study shows that HOTAIR lncRNA independently of PRC2 redistributes LSD1 along chromatin genome‐wide and thus impairs Lsd1 function in maintaining epithelial identity.